การพัฒนามาตรวัดเมตาคอคนิชั่นโดยใช้คอมพิวเตอร์สำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 - คมกริบ ธีรานุรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purposes of this research were (1) to develop a conceptual framework and scale of metacognition, (2) to develop a Paper and Pencil Metacognition Scale (PPMs) and a Computer-Based Metacognition Scale (CBMs), (3) to construct a norm for grade six students and (4) to assess metacognition of grade six students in Bangkok and its vicinity. The sample consisted of 626 grade six students at four school jurisdictions as follows: Office of the Private Education Commission, Office of The Basic Education Commission, Department of Education Bangkok Metropolitan Administration and Department of Local Administration in academic year 2009. The research instruments are PPMs and CBMs, which is content free and task oriented test in multiple choice format. Cronbach’s alpha internal consistencies were estimated for the reliability of the scales. Pearson’s product moment correlation coefficients were examined to determine the concurrent validity. Confirmatory factor analysis was performed to determine the construct validity through LISREL. Major results of the study were as follow: (1) The developing of metacogition scale for grade six students is 15 multiple choice items and 6 tasks. Measuring in seven factors of metacognition consisted of (a) strategic knowledge, (b) cognitive task, (c) self knowledge, (d) provaluation, (e) planning, (f) monitoring and (g) evaluation. (2) The internal consistency reliability of the PPMs and CBMs are .64 and .69, respectively. The PPMs and CBMs were consistent to the empirical data. (X²[subscript PPMS] = 173.819, df[subscript PPMS] = 154, p[subscript PPMS] = .133 / X²[subscript CBMS] = 113.412, df[subscript CBMS] = 92, p[subscript CBMS] = .064) and CBMs seem to be more efficient than PPMs statistically and practically. (3) The norms of grade six students in Bangkok and its vicinity that calculate from CBMs were starting from percentile range 0 to 99 and Normal-T value ranged from 19 to 82. (4) The overall metacognition score of grade six students in Bangkok and its vicinity, by using both norm and absolute criteria, indicates a moderate level of metacognition. The products of this study were: an Individually Administered Metacogition Scale, a Paper and Pencil Metacognition Scale, a Computer-Based Metacognition Scale’s website [www.cued-cbms.com/chula/index.html] and the test manual of those three matacognition scales (IAMs, PPMs and CBMs)